Collegium Ramazzini Additional Statement Regarding the War in the Gaza Region - Collegium Ramazzini (European Journal of Oncology and Environmental Health, 2026)
Fellows of The Collegium Ramazzini are humanitarians. Our mission is “to advance the study of occupational and environmental health issues and be a bridge between the world of scientific discovery and the social and political centers which must act on the discoveries of science to protect public health.” Therefore, we must stand for protecting occupational and environmental health of all people everywhere.